2002
DOI: 10.1105/tpc.005231
|View full text |Cite
|
Sign up to set email alerts
|

Early Gene Expression Associated with the Commitment and Differentiation of a Plant Tracheary Element Is Revealed by cDNA–Amplified Fragment Length Polymorphism Analysis[W]

Abstract: Isolated mesophyll cells from Zinnia elegans are induced by auxin and cytokinin to form tracheary elements (TEs) in vitro with high synchrony. To reveal the changing patterns of gene expression during the 48 h of transdifferentiation from mesophyll to TE cell fate, we used a cDNA-amplified fragment length polymorphism approach to generate expression profiles of >30,000 cDNA fragments. Transcriptional changes of 652 cDNA fragments were observed, of which 304 have no previously described function or sequence ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 42 publications
5
85
0
1
Order By: Relevance
“…We have estimated previously that 80% of the expression patterns observed in cDNA-AFLP gels can be confirmed by reverse transcription (RT)-PCR or northern gel-blot analyses (Milioni et al, 2002). The cDNA-AFLP analysis indicated that ZeRH2.1 was first expressed 4 h after addition of auxin and cytokinin to the culture medium in the zinnia system.…”
Section: Expression Pattern Of Zerh21 During Formation Of Tracheary mentioning
confidence: 94%
See 2 more Smart Citations
“…We have estimated previously that 80% of the expression patterns observed in cDNA-AFLP gels can be confirmed by reverse transcription (RT)-PCR or northern gel-blot analyses (Milioni et al, 2002). The cDNA-AFLP analysis indicated that ZeRH2.1 was first expressed 4 h after addition of auxin and cytokinin to the culture medium in the zinnia system.…”
Section: Expression Pattern Of Zerh21 During Formation Of Tracheary mentioning
confidence: 94%
“…Using a cDNA-AFLP approach, Milioni et al (2002) isolated more than 600 transcript-derived fragments that showed differential expression during tracheary element formation in vitro. One of these was a 120-bp-long transcript-derived fragment with sequence similarity to RING domain-containing proteins of Arabidopsis (Arabidopsis thaliana).…”
Section: Expression Pattern Of Zerh21 During Formation Of Tracheary mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells grown in vitro are more accessible for study of the developmental processes associated with xylogenesis. For example, cell cultures that differentiate a high percentage of TEs can be collected at different time points after induction of TE differentiation, and the changes in cell-wall biochemistry, gene expression, and the proteome or metabolome can be investigated (Milioni et al 2002;Kubo et al 2005;Demura et al 2002;Möller et al 2005aMöller et al , 2005b. Ideally this will involve in vitro cell cultures that produce TEs in a synchronous manner to provide access to high percentages of TEs that are in specific stages of development.…”
Section: The Advantages Of Studying Tracheary Elements In Vitromentioning
confidence: 99%
“…The Zinnia system is a robust model for vascular development in plants providing a set of stage-specific marker genes for xylogenesis (Milioni et al 2002;Pesquet et al 2005). However, the major limitation of the Zinnia elegans system is that the initiation of xylogenic cultures is exclusively done from freshly isolated mesophyll.…”
Section: Tracheary Element Differentiation Using Zinnia Elegans Mesopmentioning
confidence: 99%